Analysis of the E-Procurement System of Goods and Services for the Auction of Computers and Laptops at PT Pelabuhan Indonesia (Case Study of Pelindo 1 Belawan) - Nur Delimaya; Sri Sudiarti (Penerbit Jurnal Indonesia, 2022)
Based on information from the LKPP website, the procurement of goods and services through electronic catalogs has reached a total transaction of Rp. 15 trillion in 2015. This is because the number and types of goods and services in the electronic catalog have reached more than 40,000 products and are targeted for 2019 to reach 225,000 products. PT Pelabuhan Indonesia (Persero) (doing business under the name Pelindo) is an Indonesian state-owned enterprise engaged in logistics, particularly port management and development. Currently, the company operates 94 ports located in 32 provinces in Indonesia. From West Sumatra to West Java, Pelindo has become one of the strategic SOEs where all managed ports have a significant position in the transportation of international trade networks based on sea transportation.